Językowy obraz troski o II Rzeczpospolitą utrwalony w nazwach stowarzyszeń - Marta Karamańska; Ewa Młynarczyk (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2018)
The article discusses names of associations, hitherto unresearched, from the interwar pe- riod in Poland in terms of the linguistic worldview they are a testimony to. Analysing lexical components of the names reflects great care taken of restored statehood in several domains: the Republic’s integration and firm establishment of Polishness throughout, economic and cultural development, civic education and strengthening the state’s defence.